الشيخ طه جابر العلواني وجهوده الدعوية والعلمية - العايب, بسمة; ديده, ماجده; دريهم, اشراق; فقير, عبير (جامعة الوادي university of eloued, 2019)
تناول هذا البحث دراسة علم من اعلام الدعوة الدكنتور طه جابر العلواني وجهوده - الدعوية والعلمية وقد تضمن البحث التعريف بالدكتور من ناحية العصر والاسلام والنسب - والنشاة والحياة العلمية والعملية وذكر الوفاة والارار . ثم تطرق الى جهوده الدعوية تناول فيها االدعوة من خلال الخطب والدروس والمقالات وفي الاخير تطرق االى الجهود العلمية تناول فيها الدراسات القرءانية والفكرية والفقهية والعقائدية والخاتمة كانت متضمنة لاهم النتائج المتوصل اليها من خلال البحث. Summary This research death with the study of science from the flags of the call - doctor djaber al alwani and his efforts of scientific advo cary – the reseqrch included the definition of the doctor in terns of age name descent birth . scientific and practical life qnd the mention of death and effects . He then connentch on the invitation efforts in wich the invitation taken throwgh speaches . less on and articls in the last . the scientific efforts in wich the qualuties in tellectual , fly , culture and the restructuring were add ressed , including the most important results of then throwgh the research .
دعوة